ASOSIASI ANTARA TIPE CAIRAN PARENTERAL DENGAN MUNCULNYA MANIFESTASI KLINIS FLEBITIS DI RSUD Dr. ISKAK TULUNGAGUNG (STUDI DI RUANG DAHLIA DAN FLAMBOYAN) - Islamy, Aesthetica (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2019)
Theoretical Framework: Phlebitis is one of frequently nosocomial infection, its clinical manifestation are swelling, redness, and pain along the vein. In 2006, DepKes RI reported 17.11% phlebitis cases which increased 50.11% in 2013. One of phlebitis risk factors is the type of parenteral fluid. If the treate donâ€™t handled soon, it can make antrioventricular blockage and result in death. The purpose of this research is to know the relation between the type of parenteral fluid with phlebitis which occurred in patients in Regional Public Hospital Dr. Iskak Tulungagung. The study design use cross sectional. Thirtty patients which was treated at Flamboyan and Dahlia Rooms were selected by consecutive sampling technique. The research was conducted in April until May 2017. The research instruments are observation sheet medical record. The statistical used is Chi-Square Test. The result showed that 15 respondents (50%) was treated by isotonic therapy, hypertonic 3 respondents (10%), and 12 respondents got 2 kinds of parenteral fluid (isotonic+hypertonic). Respondents with phlebitis are 9 respondents (30%). The majority occurred in patients with hypertonic therapy as much as 2 respondents (67%), 6 respondents (50%) with isotonic+hypertonic therapy, and 1 respondent (7%) with isotonic therapy. The statistic test obtained Ï value 0.017 (Î±=0,05). Conclusion there is relation between the type of parenteral fluid with phlebitis in patients at Flamboyan and Dahlia Rooms in Regional Public Hospital Dr. Iskak Tulungagung at 2017. Solution of the study result should be attempted to suppress the incidence of phlebitis, related with the inravenous catheter, for long-term installation should be given trough the central vein. Â Keywords: Parenteral Fluid, Isotonic, Hypertonic, Nosocomial Infection, Phlebitis.